(untitled) (Amsterdam,Boston, 2004)
For those basic components of physical security controls, one need look no further than the third edition of this Lawrence Fennelly work. Fennelly provides readers with a quick, easy-to-understand reference on security controls, design and management techniques. Numerous drawings capture the reader's attention and ensure that each control will be well understood and implemented correctly. .any security professional would benefit from the collection of knowledge and useful information assembled in this book, especially those seeking the newly launched ASIS Physical Security Professional Certification. - Security Management. Fennelly has tapped into the experiences of many top security professionals to get a broad brush of knowledge for his most recent book. Each chapter has good depth and detailed information that is valuable to the general practitioner. - Professional Safety
Keywords: Burglary protection,Crime prevention,Bảo vệ trộm,Phòng chống tội phạm